Neutrophil Counts in Healthy South African Infants: Implications for Enrollment and Adverse Event Grading in Clinical Trials in an African Setting - Anthonet Koen, MBBCh; Lisa Jose, MBBCh; Shabir A. Madhi, PhD; Alan Fix, MD; Stanley Cryz, PhD; Michelle J. Groome, PhD (Elsevier, 2019)
Absolute neutrophil counts are used to assess eligibility and safety during clinical trials but the toxicity grading scale used can affect enrollment and reporting of adverse events. During a trial investigating a parenteral rotavirus vaccine in South Africa, we excluded otherwise healthy infants without HIV infection from participation owing to neutropenia. Trial registration: ClinicalTrials.gov: NCT02109484.